2014
DOI: 10.2471/blt.14.135541
|View full text |Cite
|
Sign up to set email alerts
|

Proposed declassification of disease categories related to sexual orientation in theInternational Statistical Classification of Diseases and Related Health Problems(ICD-11)

Abstract: The World Health Organization is developing the 11th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-11), planned for publication in 2017. The Working Group on the Classification of Sexual Disorders and Sexual Health was charged with reviewing and making recommendations on disease categories related to sexuality in the chapter on mental and behavioural disorders in the 10th revision (ICD-10), published in 1990. This chapter includes categories for diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(48 citation statements)
references
References 29 publications
0
43
0
5
Order By: Relevance
“…Ser lésbica, gay, bissexual e transexual, ter qualquer identidade de gênero, expressão de gênero ou orientação sexual não configura doença e sim características pessoais. 6,7 A gênese das condições de saúde e adoecimento da população LGBT+, quer em sua dimensão estrutural, inter-relacional ou internalizada, encontra-se na discriminação e no estigma a que ela está submetida, bem como nas diferenças e desigualdades em saúde que a afetam. [8][9][10][11][12] Desse modo, o enfrentamento do estigma, do preconceito e da discriminação são temas centrais nos debates sobre o cuidado à saúde à população LGBT+.…”
Section: Os Pressupostos E Os Objetivos Da Oficina Sobre a Saúde Da Punclassified
“…Ser lésbica, gay, bissexual e transexual, ter qualquer identidade de gênero, expressão de gênero ou orientação sexual não configura doença e sim características pessoais. 6,7 A gênese das condições de saúde e adoecimento da população LGBT+, quer em sua dimensão estrutural, inter-relacional ou internalizada, encontra-se na discriminação e no estigma a que ela está submetida, bem como nas diferenças e desigualdades em saúde que a afetam. [8][9][10][11][12] Desse modo, o enfrentamento do estigma, do preconceito e da discriminação são temas centrais nos debates sobre o cuidado à saúde à população LGBT+.…”
Section: Os Pressupostos E Os Objetivos Da Oficina Sobre a Saúde Da Punclassified
“…Homosexuality is still illegal in 79 countries, with laws in 10 countries providing for the death penalty (see: ILGA, ). The WHO review committee for ICD‐11 2017‐18 has concluded that:
From a human rights perspective, the F66 categories selectively target individuals with gender nonconformity or a same‐sex orientation without apparent justification (Cochran et al., , p. 676).
…”
Section: From Medical To Moral; From a Sickness To A Sin?mentioning
confidence: 99%
“…From a human rights perspective, the F66 categories selectively target individuals with gender nonconformity or a same‐sex orientation without apparent justification (Cochran et al., , p. 676).…”
Section: From Medical To Moral; From a Sickness To A Sin?mentioning
confidence: 99%
“…The symposia summarized the proposals for the various sections of the chapter, which are being produced by the fourteen working groups appointed by the World Health Organization (WHO) in consultation with relevant stakeholders, including WHO's member countries, several professional groups, and users of mental health services and their families. A list of scientific papers presenting and discussing these proposals, and of other relevant publications, is provided at the end of this article .…”
mentioning
confidence: 99%